The Effectiveness of Extensive Reading Book (Local Wisdom Based) to Support English Subject at Tanjungpura University - Yusawinur Barella (Jurnal Pendidikan Bahasa, 2021)
This study aims to develop extensive reading materials based on local wisdom to support English courses at Tanjungpura University. The ADDIE model was used in the development of reading materials in this study. This study's data sources include validation sheets from English material experts, instructional design experts, media and graphic design experts, and small group evaluations of students taking English courses. The method used for data collection is a questionnaire, while the instrument used in collecting accurate data is a Likert scale. The analysis used is a descriptive qualitative analysis and quantitative descriptive analysis. The research results have been developed into extensive reading materials based on local wisdom to support English courses. The study results show that the value of 98.4% was obtained in the validation carried out by material experts, instructional design experts as 86.1%, media or graphic design experts as 92.8%, and 86% based on the results of small group trials. The numbers mean that the developed reading book is suitable for supporting English courses with minor revision.